2008
DOI: 10.1073/pnas.0806154105
|View full text |Cite
|
Sign up to set email alerts
|

Measuring internal friction of an ultrafast-folding protein

Abstract: Nanosecond laser T-jump was used to measure the viscosity dependence of the folding kinetics of the villin subdomain under conditions where the viscogen has no effect on its equilibrium properties. The dependence of the unfolding/refolding relaxation time on solvent viscosity indicates a major contribution to the dynamics from internal friction. The internal friction increases with increasing temperature, suggesting a shift in the transition state along the reaction coordinate toward the native state with more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
193
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(209 citation statements)
references
References 48 publications
15
193
0
Order By: Relevance
“…The distribution of dwell times for this intermediate can be fitted well with a single exponential with dwell time as 2.8 Â10 5 time units. On the other hand, the folding time is estimated to be around 3 Â 57 It should be kept in mind, though, that adjusting solvent viscosity is still tricky as the energy landscape could be changed.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of dwell times for this intermediate can be fitted well with a single exponential with dwell time as 2.8 Â10 5 time units. On the other hand, the folding time is estimated to be around 3 Â 57 It should be kept in mind, though, that adjusting solvent viscosity is still tricky as the energy landscape could be changed.…”
Section: Resultsmentioning
confidence: 99%
“…One expects that bonding monomers centrallylocated in the chain to experience a greater effective friction than bonding monomers located near the ends due to the greater number of local interactions through which a binding monomer drags its sterically-connected neighbors. In a similar context, the intra-chain diffusion coefficient plays an important role in diffusion-controlled intra-chain reactions such as loop closing or intra-chain catalytic processes in the Rouse, Rouse-Zimm, and other models of polymer dynamics [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that internal friction varies substantially along the folding pathway of a peptide chain which suggests a connection between friction and formation of hydrogen bonds upon folding [66]. While such studies on proteins are ubiquitous [68][69][70], there is obviously a lack of experimental data on roughness of DNA and RNA conformational transition. …”
Section: Internal Frictionmentioning
confidence: 99%